Analysis of the Current Status of Ischemic Stroke Co-morbidity and Co-morbidity Patterns in Middle-aged Based on Data from Tertiary Hospitals in Henan Province - HU Qianqian, ZHOU Tong, LIU Zhihui, PAN Ye, WANG Liuyi (Zhongguo quanke yixue, 2024)
Background Middle-aged and elderly ischemic stroke patients suffer from multiple co-morbid chronic diseases, and this co-morbidity status has a great impact on the patients' healthy living standard. Currently, there are few studies on the current status of ischemic stroke co-morbidities and the analysis of co-morbidity patterns. Objective To understand the current status of ischemic stroke co-morbidities in middle-aged and elderly people in Henan Province, and explore the association between ischemic stroke co-morbidities, so as to provide a reference basis for the management of ischemic stroke co-morbidities, as well as the preventive and control measures. Methods Ischemic stroke patients over 45 years of age attending Henan Provincial People's Hospital from January 2021 to December 2022 were selected for the study, with their chronic disease prevalence counted, the status of ischemic stroke co-morbidities was compared by different demographic characteristics, and the co-morbidity patterns of ischemic stroke in the middle-aged and elderly population were investigated using cluster analysis. Results A total of 1 685 middle-aged and elderly ischemic stroke patients were enrolled in this study, of whom 90.0% (1 516/1 685) had at least 1 co-morbid chronic disease; 13.6% (230/1 685) had 2 co-morbid chronic diseases, 26.9% (454/1 685) had 3 co-morbid chronic diseases, and 49.4% (832/1 685) had 4 or more co-morbid chronic diseases. The chronic diseases with high prevalence were hypertension in 1 047 cases (62.1%) and dyslipidemia in 755 cases (44.8%). Among ischemic stroke patients, the prevalence of co-morbidities was higher in females compared with males (χ2=14.516, P<0.05) ; the prevalence of co-morbidities tended to increase with age (χ2trend=148.889, P<0.001) ; and the prevalence of co-morbidities tended to decrease with higher education (χ2trend=30.890, P<0.001). Cluster analysis showed four patterns of co-morbidity, which were cardiovascular-metabolic patterns (hypertension, dyslipidemia, heart attack, and diabetes mellitus), patterns characterized by hepato-pulmonary-gastrointestinal-urinary disorders (chronic lung disease, renal disease, hepatic disease, gastrointestinal disorders, and urinary disorders), psychiatric-degenerative patterns (neurological or psychiatric problems, arthritis or rheumatism, disorders related to memory), and cancer. Conclusion The prevalence of co-morbidities of ischemic stroke in middle-aged and elderly people in Henan province is high, and their co-morbidity patterns include cardiovascular-metabolic patterns, patterns characterized by hepato-pulmonary-gastrointestinal-urinary disorders, psychiatric-degenerative patterns, and cancers, among which cardiovascular-metabolic patterns are more associated with ischemic stroke, and the screening and prevention of which should be better controlled.